Characterization of HiPIMS and DCMS deposited TiAlN coatings and machining performance evaluation in high speed dry machining of low and high carbon steel - Kumar, Aditya; Bauri, Rakhohari; Naskar, Anirban; Chattopadhyay, A.K. (Surface & coatings technology, 2021)
Despite having advantages like high productivity and green manufacturing, the application of high speed dry machining (HSDM) is limited because it is associated with high cutting zone temperature that expedites the tool wear. Therefore, improved coating properties are needed in HSDM. The high power impulse magnetron sputtering (HiPIMS) is the latest addition in PVD, which seems to be a promising coating technology for enhancing the performance of the coated tools. In the present study, the HiPIMS coated TiAlN tool was employed in HSDM along with a direct current magnetron sputtered (DCMS) TiAlN coated tool, to examine the prevailing ambiguity regarding their relative performance. To accomplish the objective, plain carbon steel was turned at 600 m/min for 20 s in dry mode with TiAlN coated tool deposited by HiPIMS and DCMS. Thereafter, flank wear and cutting force were investigated to evaluate the machining performance of the tools. Before machining, the physical, mechanical, and chemical properties of the coatings were assessed to correlate them with machining performance. HiPIMS coated tools showed denser coating morphology, higher hardness, and more compressive residual stress than DCMS. The surface roughness of the coatings influenced the flank wear resistance significantly, followed by the coating's hardness. A combined factor of roughness and hardness was established to correlate with flank wear resistance, which showed a good agreement with the experimental data. •HiPIMS and DCMS deposited TiAlN coated tools were characterized.•HiPIMS process yielded denser coating with higher hardness and compressive stress.•K-type substrate yielded smoother coating than P-type for both HiPIMS and DCMS.•10–50% reduction in forces was recorded while machining with smoother coatings.•Coating roughness affected the flank wear significantly followed by hardness.